Student’s Online Platforms Entrepreneurship During the COVID-19 Pandemic - Mutiara Murin; Nugraheni Putri Lestari; Salsabila Nur Azizah; Budiawati Supangkat; Margo Purnomo; Hardian Eko Nurseto (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
The combination of the pandemic and the digitization process development is considered the right combination to boost students entrepreneurial spirit in this article. Through the use of digital ethnographic methods and interviews, the factors that influence the processof starting a business include self-will, encouragement from people around, awareness of the widespread phenomenon of online shopping,the desire to increase pocket money, and the use of free time from the flexible course schedule. This article also underlines the innovationsmade by students in developing their respective businesses through the social media platforms they use, such as continuously updating thecatalog of goods sold and brand development to stand out in the market with the same goods in the hope of attracting buyers' s attention.Overall, online business using social media offers an excellent opportunity for students during this pandemic. The growth of theentrepreneurial spirit in the subject can be studied by looking at how a student uses time to become an entrepreneur.